(untitled) (European Journal of Education and Psychology, 2009)
The Early Mathematical Competence Test (EMTC) assesses mathematical knowledge for kindergarden and primary school children. The test has 3 versions, of 40 items each and measures eight aspects of mathematical competence: Concepts of comparison; Classification; Correspondence; Seriation; Using counting words, forwards and backwards; Structures counting; Resultative counting; and General knowledge of numbers. Each subtest has five questions and a total score of 40 points. The main aim of this study was the standardization of EMTC for a Spanish population, following the international reliability and validation statistical rules. The test was administered to 1053 participants aged 4 to 7 (539 male and 514 female) from 14 schools. The EMTC provides a Mathematical Competence index, has a standard prediction value, and validation and reliability scores were significant. Key words: Early math, cognition, assessment, number sense, kindergarden, primary school.